CORRELATION OF PARENTING WITH DELINQUINCY IN JUNIOR HIGH SCHOOL STUDENTS - Aini, Syarifah; Rina, khairina; Maramis, Margarita M (Biomedical Journal of Indonesia, 2019)
Juvenile delinquency is a serious problem in all countries. Adolescent involved in delinquency have the potential to be involved in serious criminality. Many factors are thought to be the cause of juvenile delinquency, one of which is family. Parenting is a parent's act of educating their children, especially in providing values and norms that influencing the child development, including antisocial behavior that is associated with delinquency. To analyze the relationship between parenting towards juvenile delinquency in a private junior high school students in Surabaya. An observational cross-sectional analytic study that correlate between parenting towards juvenile delinquency in a junior high school students in Surabaya. The sampling technique is cluster random sampling. To asses the parenting style used the Alabama parenting questionnaire (Parental Authoritory Questionaire). Juvenile delinquency was assessed by Self-Report Delinquincy questionnaire. It was found that 70% of the subjects involved in delinquency with 52.63% experienced authoritative mothering and 66.18% experienced authoritative fathering. There was no significant relationship between mothering towards juvenile delinquency. There was a significant relationship between fathering, especially authoritative fathering towards mild juvenile delinquency and authoritarian fathering towards moderate juvenile delinquency in private junior high school students in Surabaya.Conclusion:There is relationship between parenting and juvenile delinquency.